Research on the Development of E-sports Games - Sun, Jinning (Transactions on Economics, Business and Management Research, 2024)
Since the 21st century, the development of Internet technology and online games has brought new development opportunities for e-sports, which has gradually become a formal sports event. In China, e-sports has also undergone a development process from the periphery to the mainstream, and was listed as an official sports event by the General Administration of Sport of China in 2003. The profit models of e-sports are diverse, including in-game recharge, organizing competitions, advertising and linking with other products, and selling game derivatives. With the advancement of technology, especially the development of live streaming technology, the viewing and participation of esports have greatly increased. Large scale esports events have attracted millions of viewers worldwide to watch online, making esports a global cultural phenomenon. The development background of e-sports is the result of the rise of the electronic gaming industry and technological progress. It is not only a form of entertainment, but also an emerging sport that has a profound impact on the lifestyle, entertainment, and social interaction of young people. With the increasing recognition of electronic sports in society, it has become an industry with enormous commercial value and cultural influence. This article analyzes from multiple perspectives why competitive games are profitable, how to make profits, and how to better obtain profits, including why competitive games are becoming increasingly popular, the profit models of electronic sports games, and how various developments affect competitive games, as well as how to make electronic sports games develop better and better.